Impact of access to financial services, including by highlighting remittances on development : economic empowerment of women and youth (UN New YorkUS, 2014)
Centers discussions around the exchange of experiences and lessons learnt, oriented towards best-fit and coherent national and international policies, regulatory and institutional frameworks, and other measures aimed at financial inclusion. Focuses especially on remittances, particularly for the benefit of women and youth.
Keywords: FINANCIAL SERVICES